OAK OPEN FORESTS ('' DEHESA " OR '' MONTADO ") OF QUERCUS ROTUNDIFOLIA LAM . IN THE IBERIAN PENINSULA AND THEIR PRODUCTS (International Oaks, 2004)
Features dehesa, the Spanish word used to name the open forests and woodlands of Quercus species in Iberian Peninsula. Sustainability and stability in terms of ecological products; Products derived from oak open forests; Availability of products in dehesa (citation)

OAK OPEN FORESTS ('' DEHESA " OR '' MONTADO ") OF QUERCUS ROTUNDIFOLIA LAM . IN THE IBERIAN PENINSULA AND THEIR PRODUCTS - Balbuena, Enrique; Doncel, Esperanza (International Oaks, 2004)
Features dehesa, the Spanish word used to name the open forests and woodlands of Quercus species in Iberian Peninsula. Sustainability and stability in terms of ecological products; Products derived from oak open forests; Availability of products in dehesa (citation)